Incremental growth and origin of the Cretaceous Renjiayingzi pluton, southern Inner Mongolia, China: Evidence from structure, geochemistry and geochronology - Li, S.; Wilde, Simon; Wang, T.; Guo, Q. (Pergamon-Elsevier Science Ltd, 2013)
The Renjiayingzi intermediate-acid pluton is located along a pre-existing ENE–WSW-trending dextral shear zone that forms part of the Xar Moron suture zone that marks the final closure of the Paleo-Asian Ocean. The pluton is composed of three small intrusions, which from northwest to southeast, are named the Shuangjianshan (SI), the Qianweiliansu (QI) and the Xingshuwabeishan (XI) intrusions. LA-ICPMS zircon U–Pb dating of a pyroxene diorite from the SI yields an age of 138 ± 1 Ma; the SHRIMP zircon U–Pb age of a tonalite from the QI records an age of 134 ± 2 Ma, whereas LA-ICPMS zircon U–Pb dating of a monzogranite from the XI has an age of 126 ± 1 Ma, suggesting the entire pluton was built up by three separate emplacement events that young to the ESE: this is further supported by the contact relations. Incremental growth of plutons by amalgamation of repeated small magma pulses is the most viable emplacement model.The pluton was probably emplaced by updoming of the roof along previous tensile fractures and by upward stacking of the three intrusions. The SI and QI have similar U–Pb ages and geochemical characteristics, and most likely had the same magma source and underwent similar petrogenetic processes. They have high MgO concentrations at low silica contents, are enriched in large ion lithophile elements, depleted in high field strength elements, have negative eNd(t) values of 1.8 to 3.7, with Nd model ages of 1.07–1.19 Ga. Pyroxene diorites of the SI also have variable zircon eHf(t) values (from 0.8 to +6.1), indicating that they were mainly derived from juvenile crust with minor crustal contamination and clinopyroxene-dominated fractional crystallization. The late monzogranites from the XI show weak negative eNd(t) values of 2.3 to 2.5, young Nd model ages of 0.99–1.00 Ga, positive zircon eHf(t) values (+1.3 to +4.6) and higher SiO2 and K2O contents, with strong depletion in Eu, P and Ti, indicating derivation from a distinct petrogenetic process from the two earlier intrusions. The monzogranites were the result of partial melting of juvenile crust in response to mantle-derived magma underplating, together with plagioclase-dominated fractional crystallization.